Overview of Environment Sanitation Conditions of Elementary Schools in Surakarta City During the Covid-19 Transition Period - Besta Ajeng Yoga Istichomah; Dwi Astuti (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The mandatory requirements that schools must fulfill are strict implementation of health protocols, for example having adequate hand washing facilities equipped with running water and soap. However, data shows that there are still many elementary schools in Indonesia that do not have sanitation facilities that meet standards. This research aims to provide an overview of the environmental sanitation conditions of elementary schools in Surakarta City during the Covid 19 transition period. This research uses a descriptive observational method. The research was conducted in 10 elementary schools in the Surakarta City area. The research was conducted from February to March 2023. The sampling technique was random sampling. The sample in this study was 10 elementary schools. The data collection technique is by observation by filling in an observation sheet. The data analysis used is descriptive univariate analysis. The research results show that 80% of elementary schools provide hand washing facilities and soap and are equipped with a good drainage system. The cleanliness and condition of water closets in most schools meets the requirements. However, there are several elementary schools where the ratio of the number of toilets and students does not meet the requirements. There are 80% of schools where clean water sources are located and 70% of schools where the distance between water reservoirs and water closets to the canteen meets the requirements. 70% of schools have a distance between the bathroom or cafeteria and the school canteen < 10 meters. It was concluded that 10 elementary schools in the city of Surakarta were categorized as healthy schools or had good sanitation hygiene. However, there are several sanitation facilities whose existence needs to be optimized so that the level of health can increase. It is recommended for schools to ensure that school areas, including classrooms, toilets and school grounds, are cleaned regularly to prevent the accumulation of rubbish and dirt and it is recommended to provide regular education to students about the cleanliness of the school environment and provide adequate hand washing facilities. Keywords: COVID-19, environmental health inspection, elementary school, hygiene sanitation, transition period